The Influence of Price, Service Quality, and Word Of Mouth on the Purchase Decision of PT Daniel Samudra Abadi's Loading and Unloading Services - Alexandra Marcellina Harindah Siswanto (Universitas Ciputra Surabaya, 2021)
PT Daniel Samudra Abadi is a company engaged in stevedoring services. The services provided are specialized in products, such as steel (cold rolled steel sheet, steel sheet in coil, steel plate, prime concast steel slab, etc.), pulp, and general cargo. The purpose of this research is to determine the influence of price, service quality and word of mouth on the purchase decision of stevedoring service. The population in this research are consumers of PT Daniel Samudra Abadi who have used service from 2018-2020 period with 31 companies as a sample. Determination of the sample in this research using saturated samples. This research uses multiple linear regression analysis. The results showed that all independent variables, namely price, service quality and word of mouth have a positive and significant effect on the purchase decision of PT Daniel Samudra Abadi stevedoring service.